EFFECT OF USING ADDITIVES ON SOME CHEMICAL AND QUALITY PROPERTIES OF LOCAL BASTURMA DURING STORAGE - Naska A. Al-Marazany (Mesopotamia Journal of Agriculture)
This study was conducted to study the effect of using some food additives like ascorbic acid, nitrate and nitrite, sodium phosphate, lactic and acetic acid with different concentrations upon some chemical and quality properties of local basturma during storage within open climate temperature from march to june. The results of the study revealed that the value of pH was decreased in most of the treatments during storage period with increase in some treatments at the last month of storage. Treating with vitamin C with different concentrations resulted in the decrease of peroxide value, free fatty acids (FFA) and amino nitrogen during the storage period and decrease of pH from April till June. When nirate and nitrite were used , an increase of pH value, peroxide value, FFA and amino nitrogen during the storage were risen. The compact treatment {Vitamin C + nitrate and nitrite} increased significantly pH value in comparison with the control. It was found that the highest value of pH was 6.7 and 6.8 when sodium phosphate was added in concentration of 0.3% during May and June, respectively . The treatment with acetic and lactic acids resulted in a decrease of pH value, peroxide value and amino – nitrogen and an increase in the free fatty acids .